High Aspect Ratio Polymeric Nanoneedle Arrays. Issue 4 (16th April 2021) - McCormack, James C.; Podhorska, Lucia; Delaney, Colm; Zhang, Fengyuan; Rodriguez, Brian J.; Kelleher, Susan M.
Abstract : Front Cover : In article number 2000754, Susan M. Kelleher and co‐workers outline an accessible and scalable method for polyethylene glycol (PEG)‐tapered nanopillar array production. Photopolymerisation of acrylateterminated polypropylene glycol (PPG) and PEG monomeric/photoinitiator cocktails is utilised to cast high fidelity replicas of silicon nanopillar arrays. In this way, rapid prototyping of polymeric nanostructured surfaces is achieved with feature dimensions relevant to optical and antibacterial applications.